Oiling the bureaucracy? political spending, bureaucrats and the resource curse. (March 2020) - Harris, Adam S.; Sigman, Rachel; Meyer-Sahling, Jan-Hinrik; Mikkelsen, Kim Sass; Schuster, Christian
Highlights: Treating the government of oil-rich countries as unitary actors oversimplifies the process by which countries fall prey to the resource curse. Future studies must consider the role of bureaucrats and other key players in facilitating or stymying the resource curse. For practitioners, bureaucrats may constitute a potential avenue through which to constrain politicians who mismanage resource revenues. Bureaucrats secure in their jobs and outside government patronage networks are more likely to oppose the political use of oil revenue. Abstract: What role do bureaucrats play in the development of the resource curse in countries that have recently discovered oil? Much of the resource curse literature argues that political leaders spend natural resource revenue in ways that entrench their political power but undermine longer-term economic development. This literature has largely overlooked the role of bureaucrats – those responsible for the day-to-day operations of the state. Bureaucrats may support or constrain political spending in ways that minimize the resource curse. Using results of a survey experiment with over 3000 government employees in Ghana and Uganda, two countries with recent oil and gas discoveries, we find that bureaucrats treated with information on oil revenue are more likely to disapprove of spending practices that benefit political supporters. The results also suggest that material motivations may be at play: bureaucrats in Uganda who are secure in their jobs and outside of government patronage networks are most likely to oppose the political use of oil revenue. These findings challenge unitary state assumptions underlying much of the resource curse literature, especially for new oil producers. They also suggest that policymakers ought to engage civil servants in efforts to avoid or curtail the resource curse.